A Bispecific Antibody-Based Approach for Targeting Mesothelin in Triple Negative Breast Cancer - Del Bano, Joanie; Florès-Florès, Rémy; Josselin, Emmanuelle; Goubard, Armelle; Ganier, Laetitia; Castellano, Rémy; Chames, Patrick; Baty, Daniel; Kerfelec, Brigitte (Frontiers in Immunology, 2019)
Triple negative breast cancers (TNBC) remain a major medical challenge due to poor prognosis and limited treatment options. Mesothelin is a glycosyl-phosphatidyl inositol-linked membrane protein with restricted normal expression and high level expression in a large proportion of TNBC, thus qualifying as an attractive target. Its overexpression in breast tumors has been recently correlated with a decreased disease-free survival and an increase of distant metastases. The objective of the study was to investigate the relevance of a bispecific antibody-based immunotherapy approach through mesothelin targeting and CD16 engagement using a Fab-like bispecific format (MesobsFab). Using two TNBC cell lines with different level of surface mesothelin and epithelial/mesenchymal phenotypes, we showed that in vitro MesobsFab promotes the recruitment and penetration of effector cells into tumor spheroids, induces potent dose-dependent cell-mediated cytotoxicity of mesothelin-positive tumor cells, cytokine secretion and decreases cell invasiveness. In vivo, the anti-tumor effect of MesobsFab depends upon a threshold of MSLN density on target cells. Collectively our data support mesothelin as a relevant therapeutic target for the subset of TNBC that overexpresses mesothelin characterized by a low overall and disease-free survival as well as the potential of MesobsFab as antibody-based immunotherapeutics.